Fintech Regulation and Its Impact on The Islamic Banking Industry in Indonesia - Husein, Moh. Hidayatullah A. K.; Soleman, Moh Rafiq; Hasan, Jamaludin; Elvia, Evi Eka (Kunuz: Journal of Islamic Banking and Finance, 2025)
This study examines the impact of the development of Islamic financial technology (Islamic fintech) on the Islamic banking industry in Indonesia by analyzing the challenges and opportunities arising in the digital era within the existing regulatory framework. The study aims to assess the implementation of Islamic fintech based on regulations issued by the Financial Services Authority (Otoritas Jasa Keuangan), Bank Indonesia, and the Indonesian Council of Ulama, particularly in fostering fair competition within the Islamic financial industry. Employing a qualitative approach with a normative juridical method, this research analyzes relevant laws, regulations, and policy documents governing Islamic fintech and Islamic banking in Indonesia. The findings indicate that digital transformation through strategic collaboration between Islamic banks and Islamic fintech institutions has become an essential requirement for Islamic banks to remain competitive in the rapidly evolving digital financial landscape. The study highlights the importance of developing a hybrid innovation model that integrates conventional Islamic banking services with Islamic fintech solutions, including the digitalization of financing processes, the utilization of big data and artificial intelligence for risk management, and the development of platform-based digital products and services that remain compliant with Sharia principles. This study contributes to the existing literature by providing a comprehensive regulatory and strategic perspective on the transformation of Islamic banking in response to the growth of Islamic fintech in Indonesia